ACCESS TO EDUCATION WITH ONLINE LEARNING AND OPEN EDUCATIONAL RESOURCES: CAN THEY CLOSE THE GAP? - Geith, Christine; Vignare, Karen (Online Learning, 2008)
One of the key concepts in the right to education is access: access to the means to fully develop as human beings as well as access to the means to gain skills, knowledge and credentials. This is an important perspective through which to examine the solutions to access enabled by Open Educational Resources (OER) and online learning. The authors compare and contrast OER and online learning and their potential for addressing human rights “to” and “in” education. The authors examine OER and online learning growth and financial sustainability and explore potential scenarios to address the global education gap.